Use of Google Form in Support of Data Collection for Student Scientific Work - tri widayanti (STMIK Pontianak, 2020)
The creation and dissemination of questionnaires conventionally has an impact in data collection and completion of thesis for longer. While on the other hand students should be able to complete college on time. The accuracy of students completing lectures also affects the accreditation of study programs and universities. The purpose of community service implementation to foster knowledge and insight so that students can practice google form application in making questionnaires and collecting scientific work data online. Considering the number of students of the College of Economists Boedi Oetomo Pontianak who do not know how to make questionnaires using the google form application. So far, students are still using conventional methods in the manufacture and dissemination of questionnaires. The seminar was attended by 22 participants from the final semester of the Boedi Oetomo Pontianak College of Economics. Implementation of community service using lecture approach, direct practice guidance and discussion so that participants can understand the material delivered. Based on the results of Pretest and Postest showed that after the seminar all students can understand the use of google application form for the creation of questionnaires and data collection of scientific work.